PENANGGULANGAN BANJIR BANJIR SISI AIRSIDE BANDAR UDARA INTERNASIONAL JENDERAL AHMAD YANI SEMARANG - Janah, Miftakhul; Jauhari, Muhammad Tantowi; Ikhwanudin, Ikhwanudin; Rizani, Mohammad Debby (Jurnal Teknik Sipil Giratory UPGRIS, 2022)
AbstractSemarang is one of the cities that often occurs flood disaster due to very high rainy weather. This resulted in the Ahmad Yani airport runway being inundated with water as high as approximately 50 cm around the airside which could disrupt flight operations. Therefore it is necessary to have a flood prevention activity to minimize the situation. The purpose of this study is to determine the factors resulting from flooding on the airside of Ahmad Yani airport and to determine the design of short-term and long-term drainage systems. In calculating the planned flood discharge (R24) using data such as rainfall, channel measurement data, and the condition of the channel. Based on this data, the researcher will calculate the planned rainfall for the Q2, Q5, Q10, Q25, Q50, and Q100 years. To calculate the data, we use the Normal Distribution, Log Normal Distribution, Pearson III Log Distribution, and Gumbel Distribution. Then from these calculations the Gumbel distribution method was chosen because it is closer. Based on data processing using the Rational method, the peak flood discharge value (QP) is obtained when Q2 all channels are able to accommodate the planned flood discharge, Q5 there is 1 channel unable to accommodate, namely in DU1-P2, Q10 there is 1 channel unable to accommodate, namely in DU1- P2, Q25 there are 1 channel that is not able to accommodate, namely in DU1-P2, Q50 there are 2 channels that are unable to accommodate, namely in DU1-P2 and S1B-P7, Q100 there are 2 channels that cannot accommodate, namely in DU1-P2 and S1B-P7. For the short-term drainage system design for flood management, it includes: repairing damaged channels, improving the foundation of the west side BRC fence, repairing pump station access roads, improving airside embankments, and pumping operations. In the design of the long-term flood control drainage system, the dimensions of the drainage channel on the airside side are added because there are 2 (two) channels that are not able to accommodate the planned discharge at the 50-year return period (Q50) with the addition of dimensions in the channel DU1-P2 b = 3, 5 h = 0.5 and S1B-P7 b = 2.7 h = 0.9.Keywords: Flood, Ej Gumbel, prevention.